Exogenous NADPH ameliorates myocardial ischemia–reperfusion injury in rats through activating AMPK/mTOR pathway - Zhu Jiang; Wang Yi-fei; Chai Xiao-ming; Qian Ke; Zhang Ling-wei; Peng Peng; Chen Pei-min; Cao Jian-fang; Qin Zheng-hong; Sheng Rui; Xie Hong (Acta Pharmacologica Sinica, 2020)
Our previous study shows that nicotinamide adenine dinucleotide phosphate (NADPH) plays an important role in protecting against cerebral ischemia injury. In this study we investigated whether NADPH exerted cardioprotection against myocardial ischemia/reperfusion (I/R) injury. To induce myocardial I/R injury, rats were subjected to ligation of the left anterior descending branch of coronary artery for 30 min followed by reperfusion for 2 h. At the onset of reperfusion, NADPH (4, 8, 16 mg· kg−1·d−1, iv) was administered to the rats. We found that NADPH concentrations in plasma and heart were signiﬁcantly increased at 4 h after intravenous administration. Exogenous NADPH (8−16 mg/kg) signiﬁcantly decreased myocardial infarct size and reduced serum levels of lactate dehydrogenase (LDH) and cardiac troponin I (cTn-I). Exogenous NADPH signiﬁcantly decreased the apoptotic rate of cardiomyocytes, and reduced the cleavage of PARP and caspase-3. In addition, exogenous NADPH reduced mitochondrial vacuolation and increased mitochondrial membrane protein COXIV and TOM20, decreased BNIP3L and increased Bcl-2 to protect mitochondrial function. We conducted in vitro experiments in neonatal rat cardiomyocytes (NRCM) subjected to oxygen–glucose deprivation/restoration (OGD/R). Pretreatment with NADPH (60, 500 nM) signiﬁcantly rescued the cell viability and inhibited OGD/R-induced apoptosis. Pretreatment with NADPH signiﬁcantly increased the phosphorylation of AMPK and downregulated the phosphorylation of mTOR in OGD/R-treated NRCM. Compound C, an AMPK inhibitor, abolished NADPH-induced AMPK phosphorylation and cardioprotection in OGD/R-treated NRCM. In conclusion, exogenous NADPH exerts cardioprotection against myocardial I/R injury through the activation of AMPK/mTOR pathway and inhibiting mitochondrial damage and cardiomyocyte apoptosis. NADPH may be a potential candidate for the prevention and treatment of myocardial ischemic diseases.